2015
DOI: 10.1159/000439398
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Endoscopic Ultrasound-Guided Fine-Needle Aspiration Biopsy Specimens: Adequate Diagnostic Yield and Accuracy Can Be Achieved without On-Site Evaluation

Abstract: Background: Endoscopic ultrasound-guided fine-needle aspiration biopsy (EUS-FNA) is the preferred method for biopsying the gastrointestinal tract, and rapid on-site cytological evaluation is considered standard practice. Our institution does not perform on-site evaluation; this study analyzes our overall diagnostic yield, accuracy, and incidence of nondiagnostic cases to determine the validity of this strategy. Design: Data encompassing clinical information, procedural records, and cytological assessment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Although this study revealed comparable diagnostic yield and inadequate specimen during EUS–FNA with and without ROSE, the on‐site evaluation group required fewer passes as compared to the EUS–FNA without on‐site evaluation. Another study by O'Connor et al revealed similar finding although they compared their data of EUS–FNA without on‐site evaluation with the published literature's data of EUS–FNA with on‐site evaluation which incorporates bias into the study.…”
Section: Discussionmentioning
confidence: 76%
“…Although this study revealed comparable diagnostic yield and inadequate specimen during EUS–FNA with and without ROSE, the on‐site evaluation group required fewer passes as compared to the EUS–FNA without on‐site evaluation. Another study by O'Connor et al revealed similar finding although they compared their data of EUS–FNA without on‐site evaluation with the published literature's data of EUS–FNA with on‐site evaluation which incorporates bias into the study.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, a Dutch group studied the impact of ROSE during EUS-FNA of mediastinal and abdominal lymph nodes; the multicenter, randomized trial showed that EUS-FNA with and without ROSE were comparable in terms of diagnostic yield and accuracy [23]. When EUS-FNA is performed by a skilled endosonographer in a center with a high diagnostic rate, ROSE may offer no benefit to the standard approach [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The pooled sensitivity and specificity of two cohorts (ROSE and non-ROSE) were compared using the bivariate approach. In addition, a summary receiver operating characteristic (SROC) curve was constructed using the DerSimonian–Laird random-effects model[ 17 ] Statistical analyses were executed by Review manager5.3 (The Cochrane Collaboration, Oxford, UK) and Meta-DiSc version 1.4 statistical software (Meta-DiSc, Unit of Clinical Biostatistics team of the Ramony Cajal Hospital, Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%